Business strategy over the industry lifecycle - Baum, Joel A. C.; McGahan, Anita M. (Emerald, 2004)
The field of Strategic Management has explored a range of new questions regarding technical change, firm capabilities, and executive decision-making, producing insights into the development of firms and unfolding of competition over time. These insights point to the importance of industry context and technical change, but little research deals systematically with the interaction between such contingencies and strategic choice. This volume explores the relationship between business strategy and the industry lifecycle competitive interaction. The contributors to this volume ask, What kinds of firm capabilities are required to compete effectively in the various stages of the industry lifecycle?. Rather than focusing on generalized principles of interaction, they ask, How do firms build these capabilities, and where to they come from?. Their answers expand our understanding of the relationships between industry evolution, technical change, and business strategy, as well as industry life cycle itself.